Polyol cellulose composite phase change material and preparation method thereof
By using layered cellulose coating and hexagonal boron nitride hydroxylation modification technology in polyol phase change materials, the problems of easy leakage of materials and low thermal conductivity are solved, and a polyol cellulose composite phase change material with high thermal conductivity and good packaging rate is achieved, which is suitable for a variety of thermal management applications.
Patent Information
- Application Number
- CN202411402598.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-02-25
AI Technical Summary
Existing polyol phase change materials are prone to leakage during storage and have low thermal conductivity, which cannot effectively solve the problem of thermal energy storage and utilization efficiency.
Laminated cellulose is used to coat the polyol, and hexagonal boron nitride is added for hydroxylation modification to improve thermal conductivity and dispersion properties. At the same time, cellulose is used as a skeleton to solve the problem of easy material leakage.
The thermal conductivity of polyol cellulose composite phase change material has been improved, with a maximum increase of 60%, and it is kept at 140℃ for 1 hour without leakage. It has a good packaging rate and is suitable for thermal management of electronic equipment, solar water heater systems and other fields.
Smart Images

Figure CN119505373A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of energy storage phase change materials, and in particular to a hydroxyboron nitride polyol cellulose composite phase change material and a preparation method thereof. Background Art
[0002] Environmental problems caused by the use of fossil energy have attracted widespread attention. In order to reduce environmental pollution and promote sustainable development, the use of renewable energy has received great attention in recent years. Thermal energy, as one of the important forms of energy, accounts for about 60% of current energy consumption. However, the waste and uninterrupted supply of thermal energy lead to low energy utilization efficiency and mismatch between supply and demand. In order to improve the utilization efficiency of energy, thermal energy storage technology has been applied. Among them, latent heat storage technology based on phase change materials has been widely studied.
[0003] Phase change materials are mainly divided into inorganic and organic phase change materials. Organic phase change materials, especially polyols, have the advantages of high heat storage density and good biocompatibility and have been widely studied. Patent CN116218477A discloses a method for preparing a nanocellulose-based cooling phase change material. The patent uses epichlorohydrin to chemically crosslink nanocellulose, and then uses calcium ions for physical crosslinking to obtain a nanofiber hydrogel material, which is then modified with dopamine to obtain an aerogel material. The polydopamine-modified nanocellulose composite aerogel is then impregnated with molten polyethylene glycol under vacuum to obtain a nanocellulose composite cooling material. However, polyol phase change materials generally have the problems of easy leakage and low thermal conductivity during storage. Summary of the invention
[0004] The embodiment of the present application provides a method for preparing a polyol-cellulose composite phase change material, in which layered cellulose is used to coat the polyol, hexagonal boron nitride is added to improve the thermal conductivity, and the hexagonal boron nitride is hydroxylated to further improve the thermal conductivity of the dispersion performance and increase the hydrogen bonds between the polyol and the polyol to reduce the loss of latent heat. At the same time, cellulose is used as a skeleton to solve the problem of easy leakage of phase change materials in related technologies.
[0005] In a first aspect, the present application provides a method for preparing a hydroxyboron nitride thermally conductive enhanced polyol cellulose composite phase change material, comprising the following steps:
[0006] S101, adding 1-allyl-3-methylimidazole chloride to the soluble pulp, heating and dissolving, and obtaining a cellulose solution;
[0007] S102, cooling the cellulose solution to room temperature, adding deionized water for washing, and obtaining a cellulose hydrogel;
[0008] S103, adding hexagonal boron nitride to a sodium hydroxide aqueous solution, heating and stirring, filtering and washing to obtain hydroxy boron nitride, mixing the hydroxy boron nitride and the polyol evenly, and heating until the polyol is completely melted;
[0009] S104, soaking the cellulose hydrogel in a polydopamine solution, and after soaking, washing it with deionized water for several times to obtain a polydopamine cellulose hydrogel, and adding the polydopamine cellulose hydrogel into molten polyol for immersion to obtain a polyol cellulose composite phase change material.
[0010] In some embodiments, in step S101, the heating temperature is 80-90°C and the dissolving time is 0.5h.
[0011] In some embodiments, the mass ratio of soluble pulp to 1-allyl-3-methylimidazole chloride is 1:49.
[0012] In some embodiments, the concentration of sodium hydroxide is 5 mol / L, the water bath temperature is 95° C., and the stirring time is 12 h.
[0013] In some embodiments, the polyol is a mixture of one or more of erythritol, mannitol, tretol, and sorbitol.
[0014] In some embodiments, the polydopamine cellulose hydrogel is added to the molten polyol and immersed for 2 hours.
[0015] In a second aspect, the present application also provides a polyol cellulose composite phase change material prepared using the above preparation method.
[0016] On the third aspect, the present application also provides applications of the above-mentioned polyol cellulose composite phase change material, which can be specifically used in the fields of electronic equipment thermal management, solar water heating systems, building materials, etc.
[0017] The present application uses cellulose hydrogel, boron nitride, and polyol to prepare a polyol-cellulose composite phase change material: (1) Boron nitride is hydroxylated with sodium hydroxide to obtain hydroxyl boron nitride; (2) Polyol and hydroxyl boron nitride are mixed and heated until the polyol is melted, and then the cellulose hydrogel is immersed in the molten polyol hydroxyl boron nitride. The polyol and water complete solvent exchange and enter the pores of the hydrogel, thereby obtaining a polyol-cellulose composite phase change material with high thermal conductivity, high polyol loading, and good encapsulation rate.
[0018] The beneficial effects of the technical solution provided by this application include:
[0019] 1. The present application adopts a layered cellulose composite dopamine support skeleton, which can increase the loading amount of the polyol phase change material (up to 89%), and on the other hand, the thermal conductivity of the polyol cellulose hydroxyl boron nitride composite phase change material is increased by up to 60% relative to the pure polyol material;
[0020] 2. The polyol cellulose hydroxyl boron nitride composite phase change material prepared in this application can be kept at 140°C for 1 hour without leakage, and the encapsulation rate is good;
[0021] 3. The polyol cellulose hydroxyl boron nitride composite phase change material prepared in the present application exhibits thermal flexibility when heated to near the melting point of the polyol;
[0022] 4. The polyol cellulose composite phase change material prepared in the present application has a simple process, short reaction time, no need for post-treatment, low production cost, and is easy for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0024] Figure 1 This is the DSC curve of the polyol cellulose composite phase change material prepared in Example 1 of the present application. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0026] The embodiment of the present application provides a method for preparing a polyol cellulose composite phase change material, which can solve the problems of easy leakage and low thermal conductivity of the phase change material in the prior art.
[0027] The present invention provides a method for preparing a polyol cellulose composite phase change material, comprising the following steps:
[0028] Step S101, adding 1-allyl-3-methylimidazole chloride to the soluble pulp at a mass ratio of 1:49, heating to 80-90° C. to dissolve for 0.5 h, to obtain a cellulose solution;
[0029] Step S102, cooling the cellulose solution to room temperature, adding deionized water for washing, and obtaining a cellulose hydrogel;
[0030] Step S103, adding hexagonal boron nitride to a 5 mol / L sodium hydroxide aqueous solution, heating at 95-100° C. and stirring for 12-14 hours, filtering and washing to obtain hydroxy boron nitride, mixing the hydroxy boron nitride and the polyol evenly, and heating until the polyol is completely melted;
[0031] Step S104, soaking the cellulose hydrogel in a polydopamine solution, washing it with deionized water for several times to obtain a polydopamine cellulose hydrogel, and then adding the polydopamine cellulose hydrogel into molten polyol for immersion to obtain a polyol cellulose composite phase change material.
[0032] In the above preparation process, the polyol is a mixture of one or more of erythritol, mannitol, tretol, and sorbitol, and the experimental raw materials are all commercially available.
[0033] The polyol cellulose composite phase change material and the preparation method thereof provided in the present application are described in detail below in combination with embodiments and comparative examples.
[0034] Embodiment 1:
[0035] Example 1 provides a method for preparing a polyol cellulose composite phase change material, comprising the following steps:
[0036] (1) Weigh 0.8 g of soluble pulp, add 39.2 g of 1-allyl-3-methylimidazole chloride, and dissolve at 80° C. for 0.5 h to prepare a cellulose solution;
[0037] (2) When the cellulose solution is cooled to room temperature, deionized water is added for washing to obtain a cellulose hydrogel;
[0038] (3) adding 0.5 g of hexagonal boron nitride to 200 mL of 5 mol / L sodium hydroxide aqueous solution, heating to 95° C. and stirring for 12 h, filtering and washing to obtain hydroxyboron nitride, mixing the hydroxyboron nitride with 50 g of erythritol, and then melting at 130° C.;
[0039] (4) Soaking the cellulose hydrogel in a polydopamine solution, and after soaking, washing it with deionized water for several times to obtain a polydopamine cellulose hydrogel, and then immersing the polydopamine cellulose hydrogel in the molten erythritol solution of step (3) for 2 hours to obtain a polyol cellulose composite phase change material.
[0040] The DSC curve of the polyol cellulose composite phase change material prepared in Example 1 is as follows: Figure 1 As shown, from Figure 1 It can be seen that the latent heat of the composite phase change material prepared in Example 1 is as high as 318.7 J / g; when the composite phase change material is heated to 140° C. and maintained for 1 hour, no molten erythritol leaks.
[0041] Comparative Example 1:
[0042] (1) Weigh 0.8 g of soluble pulp, add 39.2 g of 1-allyl-3-methylimidazole chloride, and dissolve at 80° C. for 0.5 h to prepare a cellulose solution;
[0043] (2) When the cellulose solution is cooled to room temperature, deionized water is added for washing to obtain a cellulose hydrogel;
[0044] (3) The cellulose hydrogel is immersed in a polydopamine solution. After the immersion, it is washed several times with deionized water to obtain a polydopamine cellulose hydrogel. 50 g of erythritol is weighed and melted at 130° C., and then the polydopamine cellulose hydrogel is immersed in the molten erythritol solution for 2 hours to obtain a polyol cellulose composite phase change material.
[0045] The latent heat of the composite phase change material prepared in Comparative Example 1 is as high as 262.5 J / g; the composite phase change material is heated to 200° C. and maintained for 1 hour, and no molten erythritol leaks.
[0046] Embodiment 2:
[0047] Example 2 provides a method for preparing a polyol cellulose composite phase change material, comprising the following steps:
[0048] (1) Weigh 0.8 g of soluble pulp, add 39.2 g of 1-allyl-3-methylimidazole chloride, and dissolve at 85° C. for 0.5 h to prepare a cellulose solution;
[0049] (2) When the cellulose solution is cooled to room temperature, deionized water is added for washing to obtain a cellulose hydrogel;
[0050] (3) adding 0.6 g of hexagonal boron nitride to 200 mL of 5 mol / L sodium hydroxide aqueous solution, heating to 100° C. and stirring for 14 h, filtering and washing to obtain hydroxyboron nitride, mixing the hydroxyboron nitride with 30 g of mannitol, and then melting at 180° C.;
[0051] (4) Soaking the cellulose hydrogel in a polydopamine solution, and after soaking, washing it with deionized water for several times to obtain a polydopamine cellulose hydrogel; then immersing the polydopamine cellulose hydrogel in the molten mannitol solution of step (3) for 2 hours to obtain a polyol cellulose composite phase change material.
[0052] The latent heat of the composite phase change material prepared in Example 2 is as high as 298.6 J / g; the composite phase change material is heated to 140° C. and maintained for 1 hour without leakage of molten mannitol.
[0053] Embodiment 3:
[0054] Example 3 provides a method for preparing a polyol cellulose composite phase change material, comprising the following steps:
[0055] (1) Weigh 0.8 g of soluble pulp, add 39.2 g of 1-allyl-3-methylimidazole chloride, and dissolve at 82° C. for 0.5 h to prepare a cellulose solution;
[0056] (2) When the cellulose solution is cooled to room temperature, deionized water is added for washing to obtain a cellulose hydrogel;
[0057] (3) adding 0.7 g of hexagonal boron nitride to 200 mL of 5 mol / L sodium hydroxide aqueous solution, heating to 100° C. and stirring for 12 h, filtering and washing to obtain hydroxyboron nitride, mixing the hydroxyboron nitride with 20 g of erythritol and then melting at 130° C.;
[0058] (4) Soaking the cellulose hydrogel in a polydopamine solution, and then washing it with deionized water for several times to obtain a polydopamine cellulose hydrogel; then immersing the polydopamine cellulose hydrogel in the molten erythritol solution of step (3) for 2 hours to obtain a polyol cellulose composite phase change material.
[0059] The latent heat of the composite phase change material prepared in Example 3 is as high as 282 J / g; the composite phase change material is heated to 140° C. and maintained for 1 hour without leakage of molten erythritol.
[0060] Embodiment 4:
[0061] Example 4 provides a method for preparing a hydroxyboron nitride thermally conductive enhanced polyol cellulose composite phase change material, comprising the following steps:
[0062] (1) Weigh 0.8 g of soluble pulp, add 39.2 g of 1-allyl-3-methylimidazole chloride, and dissolve at 80° C. for 0.5 h to prepare a cellulose solution;
[0063] (2) When the cellulose solution is cooled to room temperature, deionized water is added for washing to obtain a cellulose hydrogel;
[0064] (3) adding 0.8 g of hexagonal boron nitride to 200 mL of 5 mol / L sodium hydroxide aqueous solution, heating to 95° C. and stirring for 12 h, filtering and washing to obtain hydroxyboron nitride, mixing the hydroxyboron nitride with 40 g of sweet alcohol, and then melting at 190° C.;
[0065] (4) Soaking the cellulose hydrogel in a polydopamine solution, and washing it with deionized water several times to obtain a polydopamine cellulose hydrogel; then immersing the polydopamine cellulose hydrogel in the molten sweet alcohol solution of step (3) for 2 hours to obtain a polyol cellulose composite phase change material.
[0066] The latent heat of the composite phase change material prepared in Example 4 is as high as 265.8 J / g; the composite phase change material is heated to 140° C. and maintained for 1 hour without leakage of molten sweet alcohol.
[0067] Embodiment 5:
[0068] Example 5 provides a method for preparing a polyol cellulose composite phase change material, comprising the following steps:
[0069] (1) Weigh 0.8 g of soluble pulp, add 39.2 g of 1-allyl-3-methylimidazole chloride, and dissolve at 88° C. for 0.5 h to prepare a cellulose solution;
[0070] (2) When the cellulose solution is cooled to room temperature, deionized water is added for washing to obtain a cellulose hydrogel;
[0071] (3) adding 1.0 g of hexagonal boron nitride to 200 mL of 5 mol / L sodium hydroxide aqueous solution, heating to 95° C. and stirring for 12 h, filtering and washing to obtain hydroxyboron nitride, mixing the hydroxyboron nitride with 60 g of sorbitol, and then melting at 120° C.;
[0072] (4) Soaking the cellulose hydrogel in a polydopamine solution, and after soaking, washing it with deionized water for several times to obtain a polydopamine cellulose hydrogel; then immersing the polydopamine cellulose hydrogel in the molten sorbitol solution of step (3) for 2 hours to obtain a polyol cellulose composite phase change material.
[0073] The latent heat of the composite phase change material prepared in Example 5 is as high as 253.1 J / g; the composite phase change material is heated to 140° C. and maintained for 1 hour without leakage of molten sorbitol.
[0074] The basic properties of the composite phase change materials prepared in Examples 1 to 5 and Comparative Example 1 are shown in Table 1.
[0075] Table 1: Basic performance data of composite phase change materials prepared in Examples 1 to 5 and Comparative Example 1
[0076]
[0077] It can be seen from Table 1 that with the increase in the amount of hydroxyboron nitride added, the thermal conductivity of the composite phase change material increases and the latent heat decreases, and the comprehensive performance of the composite phase change material obtained in Example 1 is the best.
[0078] In the description of this specification, the description with reference to the terms "one embodiment / method", "some embodiments / methods", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment / method or example are included in at least one embodiment / method or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment / method or example. Moreover, the specific features, structures, materials or characteristics described may be combined in a suitable manner in any one or more embodiments / methods or examples. In addition, those skilled in the art may combine and combine the different embodiments / methods or examples described in this specification and the features of the different embodiments / methods or examples, unless they are contradictory.
[0079] It should be noted that, in the present application, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of more restrictions, the elements defined by the sentence "comprise one..." do not exclude the existence of other identical elements in the process, method, article or equipment including the elements. In the present application, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically stipulated.
[0080] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A method for preparing a polyol cellulose composite phase change material, characterized in that: The following steps are involved: S101, adding 1-allyl-3-methylimidazole chloride to the soluble pulp, heating and dissolving, and obtaining a cellulose solution; S102, cooling the cellulose solution to room temperature, adding deionized water for washing, and obtaining a cellulose hydrogel; S103, adding hexagonal boron nitride to a sodium hydroxide aqueous solution to obtain hydroxy boron nitride, uniformly mixing the hydroxy boron nitride and a polyol, and heating until the polyol is completely melted; S104, soaking the cellulose hydrogel in a polydopamine solution, and after soaking, washing it with deionized water for several times to obtain a polydopamine cellulose hydrogel, and then adding the polydopamine cellulose hydrogel into molten polyol for immersion to obtain a polyol cellulose composite phase change material.
2. The method for preparing a polyol-cellulose composite phase change material according to claim 1, characterized in that: In step S101, the heating temperature is 80-90°C and the dissolving time is 0.5h.
3. The method for preparing a polyol-cellulose composite phase change material according to claim 1, characterized in that: The mass ratio of soluble pulp to 1-allyl-3-methylimidazole chloride is 1:
49.
4. The method for preparing a polyol-cellulose composite phase change material according to claim 1, characterized in that: The concentration of the sodium hydroxide is 5 mol / L.
5. The method for preparing a polyol-cellulose composite phase change material according to claim 1, characterized in that: The polyol is a mixture of one or more of erythritol, mannitol, tretol and sorbitol.
6. The method for preparing a polyol-cellulose composite phase change material according to claim 1, characterized in that: The polydopamine cellulose hydrogel was added into the molten polyol and immersed for 2 h.
7. A polyol cellulose composite phase change material, characterized in that: The method is prepared by the preparation method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Preparation method of nanocellulose-based cooling phase change material
CN116218477A